Quantifying links between instream woody habitat and freshwater fish species in south‐eastern Australia to inform waterway restoration. Issue 7 (4th June 2020) - Tonkin, Zeb; Kitchingman, Adrian; Fanson, Ben; Lyon, Jarod; Ayres, Renae; Sharley, Joanne; Koster, Wayne M.; O'Mahony, Justin; Hackett, Graeme; Reich, Paul; Hale, Robin
Abstract: Removal of instream woody habitat (IWH) is one factor attributed to declines in fish populations worldwide. Restoration of IWH to help fish populations recover is now common; however, quantitative predictions about the outcomes of these interventions is rare. As such, quantitative links between IWH and fish abundance is of interest to managers to inform conservation and restoration activities. Links between instream habitat attributes, especially IWH, and selected fish species of recreational, cultural, and ecological significance were explored at 335 sites spanning eight streams across south‐eastern Australia. Data were collected on fish abundance and length, IWH density and a range of other habitat attributes at a scale that incorporated at least one of each of the major mesohabitat types (functional river elements). The data were analysed using Bayesian hierarchical generalized linear mixed models to examine fish habitat associations and used to make quantitative predictions of responses to future restoration. Strong positive relationships were found between fish abundance and IWH density and the strength of this relationship varied between species and waterways. Murray cod ( Maccullochella peelii ), a species commonly targeted by IWH interventions, displayed the strongest association with IWH density. River blackfish ( Gadopsis marmoratus ) also showed a significant relationship with IWH, but this effect was waterway specific. Fish length was only related to IWH for river blackfish. These results may reflect differences in the life histories of these two species. We suggest that differences in habitat association through ontogeny may be more relevant at smaller spatial scales. The results generated in this study can be used to guide waterway restoration and develop quantitative predictions about how fish might respond to IWH interventions across south‐eastern Australia. This approach provides a powerful quantitative framework within which to explore management options and objectives, and to test our predicted responses to habitat restoration.